2010
DOI: 10.1002/jlcr.1843
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous deuteriodeiodination of iodinated tyrosine in angiotensin‐I using synthesized triethyl[2H]silane and Pd(0)

Abstract: In our efforts to develop new reactions for the efficient labelling of peptides and proteins with tritium, we now report the use of silane hydrides together with homogenous Pd(0) catalysis for the protio-and deuteriodeiodination of an o-iodo-tyrosine containing peptide (angiotensin-I) performed at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Hydrosilanes (R 3 SiH) are ubiquitous reagents in academia and industry and undergo addition reactions to a variety of unsaturated bonds (hydrosilylation) and reductions of carbon–halogen bonds. They offer several advantages, including air and moisture tolerance and low toxicity, compared to metallohydrides or tin hydrides. Hydrosilanes can be replaced by deuterosilanes (R 3 SiD) containing Si–D bonds to synthesize a wide range of deuterium-labeled carbon compounds. In addition, deuterated silanes are an important mechanistic probe for investigating the deuterium kinetic isotope effect in transformations including hydrosilylation, ortho -silylation, , and reduction of carbon-halogen , and carbon-carbon multiple bonds. Traditionally, deuterosilanes have been accessed via the reduction of halosilanes with stoichiometric amounts of expensive metallo-deuteride reagents, for example, NaBD 4 or LiAlD 4 , which produce metal salts as waste. Direct deuteration of Si–H bonds of hydrosilanes with deuterium (D 2 ) is an attractive alternative strategy to prepare deuterosilanes, and many precious transition metal catalysts have been reported for this transformation. These protocols are mostly limited to the H/D exchange in tertiary silanes, and only three examples are known to retain the activity for primary and secondary silanes. A single rhodium­(III) catalyst described by Carmona et al was shown to be active for Si–H/D exchange of an aliphatic secondary hydrosilane (Et 2 SiH 2 ) …”
Section: Introductionmentioning
confidence: 99%
“…Hydrosilanes (R 3 SiH) are ubiquitous reagents in academia and industry and undergo addition reactions to a variety of unsaturated bonds (hydrosilylation) and reductions of carbon–halogen bonds. They offer several advantages, including air and moisture tolerance and low toxicity, compared to metallohydrides or tin hydrides. Hydrosilanes can be replaced by deuterosilanes (R 3 SiD) containing Si–D bonds to synthesize a wide range of deuterium-labeled carbon compounds. In addition, deuterated silanes are an important mechanistic probe for investigating the deuterium kinetic isotope effect in transformations including hydrosilylation, ortho -silylation, , and reduction of carbon-halogen , and carbon-carbon multiple bonds. Traditionally, deuterosilanes have been accessed via the reduction of halosilanes with stoichiometric amounts of expensive metallo-deuteride reagents, for example, NaBD 4 or LiAlD 4 , which produce metal salts as waste. Direct deuteration of Si–H bonds of hydrosilanes with deuterium (D 2 ) is an attractive alternative strategy to prepare deuterosilanes, and many precious transition metal catalysts have been reported for this transformation. These protocols are mostly limited to the H/D exchange in tertiary silanes, and only three examples are known to retain the activity for primary and secondary silanes. A single rhodium­(III) catalyst described by Carmona et al was shown to be active for Si–H/D exchange of an aliphatic secondary hydrosilane (Et 2 SiH 2 ) …”
Section: Introductionmentioning
confidence: 99%
“…Hydridosilanes add to a variety of unsaturated bonds (hydrosilylation) and reduce carbon–halogen bonds. By replacing hydrosilanes, R 3 SiH, with their deuterium analogs, R 3 SiD, a wide range of deuterium-labeled carbon compounds can be synthesized. Despite these advantages, use of deuterated silanes as isotopic labeling reagents is still limited, most probably owing to the scarcity of methods for efficient catalytic direct H/D exchange reactions at silicon centers, which leaves NaBD 4 or LiAlD 4 reduction of halosilanes as the commonly used method of synthesis of deuterated silanes . Recently, several novel methods for the catalytic deuteration of silanes with D 2 using transition metal catalysts has been reported. However, all of these catalysts have relatively elaborate ligands (i.e., a , b , c , and d in Chart ), which are less easily accessible than the simple phosphines used here; for example, a cationic (η 5 -C 5 Me 5 )­Rh­(III) complex ( a ) and an iridium complex with N -heterocyclic carbene ligands ( b ) have been recently reported to catalyze the direct deuteration of silanes using D 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the tritiodehalogenation reaction may fail or produce low radiochemical yields when large peptides, conjugated peptides and proteins are subjected to heterogeneous catalysis . This led us to initiate the investigation on the use of a homogeneous catalyst together with a synthesised silane (weak hydride donor) for the same reaction . However, the synthesis of silanes from gaseous tritium is a fairly laborious process because it requires the synthesis of lithium tritide and subsequent reaction with strongly electrophilic chlorosilane.…”
Section: Introductionmentioning
confidence: 99%